Butterfly Diversity in The Alas River of Soraya Research Station, Leuser Ecosystem, Aceh Province - Fitria Nelda Fautama; Alia Rizki; Zuriana Siregar; Suwarno Suwarno (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Butterflies are insects that live along riverbanks and belong to the Lepidoptera order. The Alas River is one of the longest rivers in Sumatra which passes through four districts in Aceh Province. Along the river banks, there are varied vegetation conditions such as secondary forests, shrubs, and sandy banks. This study aims to determine the diversity and composition of butterfly species in the Alas River, which is included in the Soraya Research Station area of the Leuser Ecosystem. The transect method was used to conduct butterfly diversity research from August to December 2020. A total of 75 species of butterflies were found in this study belonging to five families: Hesperidae, Lycaenidae, Pieridae, Papilionidae, and Nymphalidae. The butterfly compositions obtained were Nymphalidae (32 species and 134 individuals), Papilionidae (16 and 137 ), Pieridae (16 and 121), Lycaenidae (9 and 52), and Hesperidae (2 and 2). The butterfly species diversity index was categorized as high (H'= 3.763).Abstrak: Kupu-kupu merupakan serangga yang tergolong ke dalam ordo Lepidoptera yang banyak hidup di aliran sungai. Penelitian tentang keanekaragaman kupu-kupu dilakukan pada bulan Agustus - Desember 2020, sampel dikoleksi dengan menggunakan metode transek. Sungai Alas merupakan salah satu sungai terpanjang di Sumatera yang melewati empat kabupaten di Provinsi Aceh. Sepanjang tepian sungai ditumbuhi oleh berbagai jenis vegetasi membentuk hutan dan semak serta daerah yang berpasir. Studi ini bertujuan untuk mengetahui keragaman dan komposisi jenis kupu-kupu di aliran Sungai Alas yang masuk dalam wilayah Stasiun Penelitian Soraya Kawasan Ekosistem Leuser. Hasil penelitian ditemukan 75 jenis kupu-kupu yang tergolong dalam lima family yaitu Hesperidae, Lycaenidae, Pieridae, Papilionidae dan Nymphalidae. Komposisi kupu-kupu yang didapatkan berturut-turut adalah Nymphalidae (32 spesies and 134 individu), Papilionidae (16 dan 137), Pieride (16 dan 121), Lycaenidae (9 dan 52), dan Hesperidae (2 dan 2). Indeks keanekaragaman jenis kupu-kupu dikategorikan tinggi (H’= 3.8).